2023
DOI: 10.1111/ddi.13748
|View full text |Cite
|
Sign up to set email alerts
|

Past forest cover explains current genetic differentiation in the Carpathian newt (Lissotriton montandoni), but not in the smooth newt (L. vulgaris)

Abstract: AimCurrent genetic variation and differentiation are expected to reflect the effects of past rather than present landscapes due to time lags, that is, the time necessary for genetic diversity to reach equilibrium and reflect demography. Time lags can affect our ability to infer landscape use and model connectivity and also obscure the genetic consequences of recent landscape changes. In this work, we test whether past forest cover better explains contemporary patterns of genetic differentiation in two closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Time lags, that is, the number of generations between landscape perturbations and a discernible population genetic response, could be particularly severe in urban areas because a rapid pace of urbanization may prevent genetic parameters of populations from approaching new equilibrium values (Epps & Keyghobadi, 2015). However, recent work has shown that L. vulgaris rapidly responds to changes in landscape structure with no evidence for time lags (Antunes, Dudek, et al., 2023), and retains high connectivity in modified habitat, for example, forest edges (Antunes, Figueiredo‐Vázquez, et al., 2023). In city‐dwelling salamanders, Lourenço et al.…”
Section: Discussionmentioning
confidence: 99%
“…Time lags, that is, the number of generations between landscape perturbations and a discernible population genetic response, could be particularly severe in urban areas because a rapid pace of urbanization may prevent genetic parameters of populations from approaching new equilibrium values (Epps & Keyghobadi, 2015). However, recent work has shown that L. vulgaris rapidly responds to changes in landscape structure with no evidence for time lags (Antunes, Dudek, et al., 2023), and retains high connectivity in modified habitat, for example, forest edges (Antunes, Figueiredo‐Vázquez, et al., 2023). In city‐dwelling salamanders, Lourenço et al.…”
Section: Discussionmentioning
confidence: 99%